Luther, Barth, and movements of theological renewal (1918-1933) - Assel, Heinrich 1961-; McCormack, Bruce L. 1952- (Theologische Bibliothek Töpelmann, 2020)
This book illuminates in a fresh way the formation, cross-fertilization, break-up, and re-organization of movements of theological renewal during the tumultuous years of the Weimar Republic. Three Protestant movements, in particular, demand our attention: the dialectical theology (Karl Barth, Friedrich Gogarten, Rudolf Bultmann); the Luther Renaissance which found adherents amongst the students of Karl Holl (Hans Joachim Iwand, Rudolf Herrmann and Emmanuel Hirsch) and Lutheran confessional movement (Werner Elert and Paul Althaus). Attention is also given to Bultmann’s close conversation-partner Martin Heidegger. Rounding out the picture thus drawn is Martin Buber, representing the Jewish Renaissance that flourished briefly in the Weimar years.